An architectural approach to level design - Totten, Christopher W. (Boca Raton : CRC, Taylor & Francis Group, 2014)
"This book discusses level design, the discipline of creating interactive game environments, with an emphasis on architectural principles. These principles can help level designers create meaningful user experiences and emotional responses for players. This involves elements of spatial psychology, human survival instincts, visual communication, and spatial storytelling, among others. Topics are discussed in a non-software specific context so readers using different types of programs can utilize the content. The book includes an overview of real-world tools and techniques that level designers will find useful in crafting their interactive worlds. "--
Includes bibliographical references and index.
Keywords: Level design (Computer science); Software architecture